Feminist Anthropology Toda: Thinking about Gendered Binaries, Violence against Women, and the Praxis of Feminist Anthropology - Baiocchi, María Lis (2024)
This entry marks our departure as Contributing Editors for the Association for Feminist Anthropology’s (AFA) column in Anthropology News (AN). We write these words as a ritual of closure serving as appointed members of the AFA Executive Board. We also write to reflect on the works we patiently, lovingly, and laboriously shepherded into publication over the past four years and what they reveal about feminist anthropology. As we bid farewell to the AFA column in AN and as we welcome the new contributing editorial duo of Maja Jeranko and Anika Jugović-Spajić to this space, we look back on our tenure to reflect on what feminist anthropologists wrote about our contemporary moment and what this work can tell us about the current state of the field.